2006
DOI: 10.1001/jama.295.22.2613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fish Oil on Ventricular Tachyarrhythmia and Death in Patients With Implantable Cardioverter Defibrillators

Abstract: clinicaltrials.gov Identifier: NCT00110838.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
114
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(121 citation statements)
references
References 31 publications
3
114
0
4
Order By: Relevance
“…In contrast to these findings, Leaf et al 20 observed a trend towards an increase in time to recurrent ventricular tachycardia or fibrillation or death in the n-3 PUFA group in the Fatty Acid Arrhythmia Trial (FAAT) in which 402 patients with an ICD were randomized to either 2.6 g/day n-3 PUFA or olive oil for 1 year. Moreover, Brouwer and coworkers 24 found no strong evidence of a protective effect of omega-3 PUFA given at a daily dose of 0.9 g for 1 year as compared to that of sunflower oil, against ventricular arrhythmias in 546 patients with ICD, although a trend towards decreased ventricular arrhythmias or death was noted in the subgroup of patients with a prior myocardial infarction. The disparate results of these studies may be related to different doses of n-3 PUFA used and background dietary fish intake, as well as heterogeneous groups of patients.…”
Section: Studies On Anti-arrhythmic Effectsmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast to these findings, Leaf et al 20 observed a trend towards an increase in time to recurrent ventricular tachycardia or fibrillation or death in the n-3 PUFA group in the Fatty Acid Arrhythmia Trial (FAAT) in which 402 patients with an ICD were randomized to either 2.6 g/day n-3 PUFA or olive oil for 1 year. Moreover, Brouwer and coworkers 24 found no strong evidence of a protective effect of omega-3 PUFA given at a daily dose of 0.9 g for 1 year as compared to that of sunflower oil, against ventricular arrhythmias in 546 patients with ICD, although a trend towards decreased ventricular arrhythmias or death was noted in the subgroup of patients with a prior myocardial infarction. The disparate results of these studies may be related to different doses of n-3 PUFA used and background dietary fish intake, as well as heterogeneous groups of patients.…”
Section: Studies On Anti-arrhythmic Effectsmentioning
confidence: 96%
“…21 The early effect of n-3 PUFA on total mortality and sudden death, as demonstrated by the time-course analysis of the results of the GISSI-Prevenzione study, supported a hypothesis of an anti-arrhythmic potential of n-3 PUFA. 22 Recently, three randomized clinical trials 20,23,24 have been performed in patients with an implantable cardioverter defibrillator (ICD), to evaluate the antiarrhythmic effects of n-3 PUFA. In the study by Raitt et al 23 no significant decrease in total mortality was observed among 200 patients with an ICD and a recent episode of sustained ventricular tachycardia or ventricular fibrillation receiving EPA/DHA 1.3g/day as compared to olive oil for 2 years.…”
Section: Studies On Anti-arrhythmic Effectsmentioning
confidence: 99%
“…However contrasting results have been reported in patients with implantable cardioverter defibrillators [24][25][26] and it is possible that n-3 FA increase risk of re-entrant tachycardia in a small and specific subset of individuals with a slow re-entrant arrhythmic loop around a region of scarred myocardium [23].…”
Section: Biological Effects Of N-3 Fa Related To Cvdmentioning
confidence: 95%
“…However, in Kowey et al's trial [37] of 663 AF patients, omega-3 supplementation did not reduce the recurrence of AF in the 6 month study period. Others have described trends towards reduction in malignant ventricular arrhythmias with omega-3 supplementation [10, [38][39][40]. Although omega-3 fatty acids appear to be effective for reducing SCD in the setting of CHD with reduced left ventricular systolic function [41], 3 trials using omega-3 fatty acids in implantable cardioverter defibrillator patients have shown mixed results [38][39][40].…”
Section: Evidence In CV Diseasementioning
confidence: 99%
“…Others have described trends towards reduction in malignant ventricular arrhythmias with omega-3 supplementation [10, [38][39][40]. Although omega-3 fatty acids appear to be effective for reducing SCD in the setting of CHD with reduced left ventricular systolic function [41], 3 trials using omega-3 fatty acids in implantable cardioverter defibrillator patients have shown mixed results [38][39][40]. The most recent trial evaluating major arrhythmic events was a substudy of the GISSI Heart Failure (HF) trial that showed fewer events in the omega-3 arm, but this finding was not statistically significant [42].…”
Section: Evidence In CV Diseasementioning
confidence: 99%